BUDAYA POLITIK PESANTREN : STUDI KASUS DI PONDOK PESANTREN MIFTAHUL HUDA KECAMATAN MANONJAYA KABUPATEN TASIKMALAYA - Edi Kusmayadi; Hendra Gunawan (Jurnal Ilmu Politik dan Pemerintahan, 2011)
Political culture, is part of the culture of the society with the characteristics of a more typical. The term includes the issue of legitimacy of political culture, power regulation, government policy-making process, the activities of political parties, the behavior of the state apparatus, and the turmoil of society against the power to rule. Political activity is also entering the world of religious, economic and social activities, personal and social life at large. Thus, political culture directly affects the political life and national decisions regarding the allocation pattern of public resources. No exception to the institution called the pesantren. Political culture in schools to some extent affect the practical political life in the boarding area itself. Pesantren and political parties actually two entities are quite far apart. Pesantren is more synonymous with education which is in contact with science and morality, while the political parties more closely on joint efforts to achieve, maintain, and seize power. Pesantren in daily life is busy with the book review that discusses the views of scholars of classical and modern about the various disciplines of Islamic religion, while political parties busy with preparing the party platform with all the strategies and political tactics to gain power for the sake of advancing the nation and state and the welfare of the people